Edukasi Masyarakat tentang Manfaat Antioksidan dari Daun Pegagan dan Daun Mint sebagai Upaya Pencegahan Stres Oksidatif dan Peningkatan Kesehatan - Anak Agung, Padmiswari; Nadya treesna wulansari; Kadek buja harditya (LOSARI DIGITAL, 2025)
This community service program aimed to enhance public knowledge of the antioxidant benefits of Centella asiatica (pegagan) and Mentha sp. (mint) as a preventive effort against oxidative stress. Conducted in Guwang Village, Gianyar Regency, the activity involved 50 participants from the general public and housewives. The program consisted of three stages: problem identification, scientific education through interactive lectures and discussions, and evaluation using pre- and post-tests. Results showed a 31% increase in participants’ knowledge regarding antioxidant functions, benefits of pegagan and mint, and healthy lifestyle practices. The program effectively linked research findings with practical community education, promoting local herbal utilization for health and economic potential.